Thermodynamic analysis of interactions of the Hsp90 with adenosine nucleotides: A comparative perspective - Minari, Karine; Azevedo, Erika Chang de; Rodrigues Kiraly, Vanessa Thomaz; Heleno Batista, Fernanda Aparecida; Moraes, Fabio Rogerio de [UNESP]; Melo, Fernando Alves de [UNESP]; Nascimento, Alessandro Silva; Gava, Lisandra Marques; Inacio Ramos, Carlos Henrique; Borges, Julio Cesar (Elsevier B.V., 2019)
Hsp90s are key proteins in cellular homeostasis since they interact with many client proteins. Several studies indicated that Hsp9Os are potential targets for treating diseases, such as cancer or malaria. It has been shown that Hsp9Os from different organisms have peculiarities despite their high sequence identity. Therefore, a detailed comparative analysis of several Hsp90 proteins is relevant to the overall understanding of their activity. Accordingly, the goal of this work was to evaluate the interaction of either ADP or ATP with recombinant Hsp9Os from different organisms ( human et and (3 isoforms, Plasmodium falciparum, Leishmania braziliensis, yeast and sugarcane) by isothermal titration calorimetry. The measured thermodynamic signatures of those interactions indicated that despite the high identity among all Hsp90s, they have specific thermodynamic characteristics. Specifically, the interactions with ADP are driven by enthalpy but are opposed by entropy, whereas the interaction with ATP is driven by both enthalpy and entropy. Complimentary structural and molecular dynamics studies suggested that specific interactions with ADP that differ from those with ATP may contribute to the observed enthalpies and entropies. Altogether, the data suggest that selective inhibition may be more easily achieved using analogues of the Hsp90-ADP bound state than those of Hsp90-ATP bound state. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Hsp90; Protein-ligand interaction; ITC; STD-NMR; Molecular dynamics